Composite separator, method for manufacturing the same, and battery

CN121394775BActive Publication Date: 2026-10-27JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511527092.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-10-27
Estimated Expiration
2045-10-24

AI Technical Summary

Technical Problem

然而无论是无机陶瓷涂层,如氧化铝、氧化硅涂层,还是聚合物涂层如聚偏二氟乙烯(PVDF)、聚甲基丙烯酸甲酯(PMMA)、聚丙烯酸酯等,均存在涂层机械强度较差及与基底间结合力较弱问题,在电池工作过程中,涂层很有可能会脱落而引起电池性能下降

Benefits of technology

在本申请实施例中,所提供的在本申请实施例的复合隔膜中,涂层包括改性陶瓷材料和天然矿物材料具有优异的热稳定性,可以提高复合隔膜的耐热性能;同时改性陶瓷材料和天然矿物材料表面含有大量的极性基团,可以提高复合隔膜对电解液的浸润性。天然矿物材料还具有丰富的纳米孔结构,可以提高复合隔膜的吸液性;部分天然矿物材料还具有二位层状结构,具有优异的离子交换性,从而提高复合隔膜的离子导电性。此外,经过改性的聚乙烯醇不仅具有亲水性还具有亲油性(其具有第二亲水基团和第二亲油基团),可以促进无机的陶瓷材料、天然矿物材料与基层的界面结合力,从而提高涂层的剥离强度。进一步地,改性聚乙醇还可以与改性陶瓷材料、天然矿物材料原位交联形成三维网络结构,提高隔膜的抗穿刺强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a composite diaphragm, a preparation method thereof and a battery. The composite diaphragm comprises a base film and a coating layer arranged on at least one side surface of the base film along the thickness direction; the coating layer comprises modified ceramic material, natural mineral material and modified polyvinyl alcohol; the modified ceramic material comprises a first hydrophilic group and a first lipophilic group; and the modified polyvinyl alcohol comprises a second hydrophilic group and a second lipophilic group. The composite diaphragm coating layer of the application contains modified ceramic material, natural mineral material and modified polyvinyl alcohol, and the three can synergistically make the diaphragm have excellent thermal stability, mechanical strength, ion conductivity and puncture resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to a composite separator, its preparation method, and a battery. Background Technology

[0002] Lithium-ion batteries (LIBs) are widely used in new energy vehicles and electronic devices due to their high energy density, long cycle life, low self-discharge rate, and lack of memory effect. The separator, as a key component of the battery, not only isolates the anode and cathode to prevent internal short circuits but also provides microporous channels for the transport of lithium ions in the liquid electrolyte. Currently, commercially available polyolefin separators, such as polyethylene (PE), polypropylene (PP), and their compounds, are widely used in lithium-ion batteries due to their excellent mechanical strength, good electrochemical stability, and reasonable cost. However, their poor thermal stability makes them prone to shrinkage at high temperatures, potentially leading to fires and explosions. Furthermore, their poor electrolyte wettability limits their application in high-performance batteries.

[0003] Currently, surface coating modification is considered a relatively effective means to improve the electrolyte wetting performance and heat resistance of polyolefin separators. However, whether it is inorganic ceramic coatings, such as alumina and silica coatings, or polymer coatings, such as polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), and polyacrylate, they all suffer from poor mechanical strength and weak adhesion to the substrate. During battery operation, the coating is likely to detach, leading to a decline in battery performance. Therefore, there is an urgent need to provide a separator that can solve the problems existing in the current technology. Summary of the Invention

[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a composite separator, a method for preparing the same, and a battery thereof. This composite separator exhibits superior ion exchange capacity, mechanical strength, and thermal stability.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: According to one aspect of this application, an embodiment of this application provides a composite membrane, including a base membrane and a coating disposed on at least one surface of the base membrane along the thickness direction; The coating comprises modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol; The modified ceramic material includes a first hydrophilic group and a first lipophilic group; The modified polyvinyl alcohol includes a second hydrophilic group and a second lipophilic group.

[0006] In some embodiments, the modified ceramic material has a particle size of 100 nm to 3 μm.

[0007] In some of these embodiments, the first hydrophilic group includes at least one of hydroxyl and amino groups.

[0008] In some embodiments, the first lipophilic group includes at least one selected from methoxy, ethoxy, methyl, ethyl, propyl, and silyl groups.

[0009] In some of these embodiments, the second hydrophilic group includes a hydroxyl group.

[0010] In some of these embodiments, the second lipophilic group comprises a siloxane group.

[0011] In some of these embodiments, the natural mineral material includes a first natural mineral material and a second natural mineral material.

[0012] In some of these embodiments, the mass ratio of the first natural mineral material to the second natural mineral material is (1~4):(1~4).

[0013] In some of these embodiments, the first natural mineral material includes at least one of halloysite, palygorskite, attapulgite, zeolite, or sepiolite.

[0014] In some of these embodiments, the first natural mineral material has a length of 0.2 μm to 3 μm and a diameter of 3 nm to 100 nm.

[0015] In some of these embodiments, the second natural mineral material includes montmorillonite.

[0016] In some of these embodiments, the particle size of the second natural mineral material is 0.4 μm to 3 μm.

[0017] In some embodiments, the coating further includes thickeners, adhesives, and additives.

[0018] In some of these embodiments, the mass ratio of the modified ceramic material, natural mineral material, modified polyvinyl alcohol, thickener, adhesive, additive and crosslinking agent is (50~80):(10~40):(2~10):(0.5~5):(3~10):(0~3):(0.03~0.4).

[0019] In some embodiments, the thickener includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, sodium alginate, guar gum, or terpineol.

[0020] In some embodiments, the adhesive includes at least one of polyacrylic acid, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyvinyl acetate, polyacrylate, polyurethane, urethane blends, or copolymers.

[0021] In some embodiments, the adjuvant includes at least one of fluoroalkyl ethoxylates, polyoxyethylene alkylamides, fatty alcohol polyoxyethylene ethers, sodium butadiene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, fatty acid glycerides, or polysorbates.

[0022] In some of these embodiments, the base film comprises a polyolefin film.

[0023] In some of these embodiments, the polyolefin includes at least one of polyethylene and polypropylene.

[0024] In some embodiments, the thickness of the base film is 3 μm to 20 μm, and the porosity is 20 to 60%.

[0025] In some embodiments, the coating thickness is 0.5 μm to 5 μm.

[0026] According to another aspect of this application, embodiments of this application provide a method for preparing a composite separator, the method comprising: Modified ceramic materials, natural mineral materials, modified polyvinyl alcohol, thickener, adhesive and additives are mixed in a solvent to obtain a suspension. Then, a crosslinking agent and catalyst are added to the suspension and mixed to obtain a coating slurry. The coating slurry is applied to at least one side surface of the base membrane to obtain a composite membrane.

[0027] In some of these embodiments, the crosslinking agent is 5% to 20% of the total mass of the suspension, based on the total mass of the suspension.

[0028] In some of these embodiments, the catalyst is 0.01% to 10% of the total mass of the suspension, based on the total mass of the suspension.

[0029] In some embodiments, the solid content of the coating slurry is 20-50%.

[0030] In some embodiments, the crosslinking agent includes at least one of glutaraldehyde or glyoxal.

[0031] In some of these embodiments, the catalyst includes at least one of hydrochloric acid or sulfuric acid.

[0032] In some embodiments, the method for preparing the modified ceramic material includes: The ceramic material is added to an alcohol solution containing a silane coupling agent, and after mixing, a suspension is obtained. After adjusting the pH value, the reaction yields the modified ceramic material.

[0033] In some embodiments, the mass ratio of the silane coupling agent to the ceramic material is (5~15):1.

[0034] In some of these embodiments, the ceramic material in the modified ceramic material includes at least one of alumina, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP, LAGP, LLZO, LCZP, or LiSICON.

[0035] In some embodiments, the silane coupling agent for silane coupling agent-modified ceramic materials includes at least one of γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane.

[0036] In some embodiments, the solid content in the suspension is 4% to 6%.

[0037] In some of these embodiments, the pH value is adjusted to 3-5.

[0038] In some of these embodiments, the reaction temperature is 50°C to 80°C and the reaction time is 2 hours to 4 hours.

[0039] In some embodiments, the preparation of the modified polyvinyl alcohol includes: Triethylene alcohol and water-soluble silicone oil are added to an aqueous solution of polyvinyl alcohol, and the reaction yields a solution containing modified polyvinyl alcohol.

[0040] In some of these embodiments, the molecular weight of the polyvinyl alcohol is 80,000 to 120,000.

[0041] In some embodiments, the polyvinyl alcohol aqueous solution has a mass fraction of 10% to 15%.

[0042] In some embodiments, the mass ratio of polyvinyl alcohol, trivinyl alcohol and water-soluble silicone oil is 100:(2~2.5):(1~1.5).

[0043] According to another aspect of this application, an embodiment of this application provides a battery including a composite separator, wherein the composite separator is the aforementioned composite separator or a composite separator prepared according to the aforementioned preparation method.

[0044] Implementing the technical solution of the present invention has at least the following beneficial effects: In this embodiment, the composite membrane provided in this application includes a coating comprising modified ceramic materials and natural mineral materials, which possess excellent thermal stability and can improve the heat resistance of the composite membrane. Simultaneously, the modified ceramic materials and natural mineral materials contain a large number of polar groups on their surfaces, which can improve the wettability of the composite membrane to the electrolyte. The natural mineral materials also possess abundant nanoporous structures, which can improve the liquid absorption of the composite membrane; some natural mineral materials also have a two-layered structure, exhibiting excellent ion exchange properties, thereby improving the ionic conductivity of the composite membrane. Furthermore, the modified polyvinyl alcohol is not only hydrophilic but also lipophilic (it possesses a second hydrophilic group and a second lipophilic group), which can promote the interfacial bonding force between the inorganic ceramic materials, natural mineral materials, and the substrate, thereby improving the peel strength of the coating. Further, the modified polyvinyl alcohol can also be in-situ crosslinked with the modified ceramic materials and natural mineral materials to form a three-dimensional network structure, improving the puncture resistance of the membrane.

[0045] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation

[0046] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.

[0047] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges or individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0048] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0049] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0050] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0051] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0052] Currently, surface coating modification is considered a relatively effective means to improve the electrolyte wetting performance and heat resistance of polyolefin separators. However, whether it is inorganic ceramic coatings, such as alumina and silica coatings, or polymer coatings, such as polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), and polyacrylate, they all suffer from poor mechanical strength and weak adhesion to the substrate. During battery operation, the coating is likely to peel off, leading to a decrease in battery performance.

[0053] [Composite diaphragm] In view of this, embodiments of this application provide a composite membrane, including a base membrane and a coating disposed on at least one surface of the base membrane along the thickness direction; The coatings include modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol; Modified ceramic materials include a first hydrophilic group and a first lipophilic group; Modified polyvinyl alcohol includes a second hydrophilic group and a second lipophilic group.

[0054] The phrase "the coating is disposed on at least one surface of the base film along its thickness direction" means that the coating can be disposed on one surface of the base film along its thickness direction, or on two surfaces of the base film along its thickness direction. Here, "surface" can be the entire area of ​​the base film or a part of the base film. As in this embodiment, the surface can be the entire area of ​​the base film. This application does not have any particular limitation in this regard, as long as the purpose of this application can be achieved.

[0055] As an example, the base film has two surfaces opposite each other in its own thickness direction, and the coating is disposed on the two opposite surfaces of the base film. It will be understood that in other embodiments, the coating may also be laminated on either of the two surfaces of the base film.

[0056] Of particular note is that in the composite diaphragm of this application embodiment, the coating, comprising modified ceramic materials and natural mineral materials, exhibits excellent thermal stability, thereby improving the heat resistance of the composite diaphragm. Simultaneously, the surfaces of the modified ceramic materials and natural mineral materials contain a large number of polar groups, which enhances the wettability of the composite diaphragm to the electrolyte. The natural mineral materials also possess abundant nanoporous structures, improving the liquid absorption of the composite diaphragm; some natural mineral materials also possess a two-layered structure, exhibiting excellent ion exchange capacity, thus improving the ionic conductivity of the composite diaphragm. Furthermore, the modified polyvinyl alcohol possesses both hydrophilic and lipophilic properties (it has a second hydrophilic group and a second lipophilic group), which can promote the interfacial bonding force between the inorganic ceramic materials, natural mineral materials, and the substrate, thereby improving the peel strength of the coating. Further, the modified polyvinyl alcohol can also be in-situ crosslinked with the modified ceramic materials and natural mineral materials to form a three-dimensional network structure, improving the puncture resistance of the diaphragm.

[0057] Based on this, the composite diaphragm coating of this application contains modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol. Their synergistic effect can give the diaphragm excellent thermal stability, mechanical strength, ionic conductivity, and puncture resistance.

[0058] In some embodiments, the particle size of the modified ceramic material is 100 nm to 3 μm. As an example, the particle size of the modified ceramic material can be 100 nm, 500 nm, 1 μm, 2 μm, 3 μm, etc., or other values ​​within the above range, and is not limited here. A particle size within this range can meet the ceramic layer thickness requirements, ensure the continuity and integrity of the ceramic coating, and meet the heat resistance requirements of the diaphragm.

[0059] In some embodiments, the first hydrophilic group includes at least one of a hydroxyl group and an amino group. As an example, the first hydrophilic group may be a hydroxyl group or an amino group.

[0060] In some embodiments, the first lipophilic group includes at least one selected from methoxy, ethoxy, methyl, ethyl, propyl, and silyl groups. As an example, the first lipophilic group may be methoxy, ethoxy, or methyl.

[0061] In some embodiments, the second hydrophilic group includes a hydroxyl group.

[0062] In some embodiments, the second lipophilic group includes a siloxane group.

[0063] In some embodiments, the modified ceramic material includes a silane coupling agent modified ceramic material.

[0064] In some embodiments, the modified polyvinyl alcohol includes polyether siloxane-grafted modified polyvinyl alcohol.

[0065] In some embodiments, the natural mineral material includes a first natural mineral material and a second natural mineral material.

[0066] In some embodiments, the mass ratio of the first natural mineral material to the second natural mineral material is (1~4):(1~4). As an example, the mass ratio of the first natural mineral material to the second natural mineral material can be 1:1, 1:2, 1:4, 2:1, etc., or other ratios within the above range, which are not limited here.

[0067] In some embodiments, the first natural mineral material includes at least one of halloysite, palygorskite, attapulgite, zeolite, or sepiolite. As an example, the first natural mineral material may be halloysite, palygorskite, or a mixture of both.

[0068] In some embodiments, the length of the first natural mineral material is 0.2 μm to 3 μm, and the diameter is 3 nm to 100 nm. As an example, the length of the first natural mineral material can be 0.2 μm, 1 μm, 2 μm, 3 μm, etc., or other values ​​within the above range, which are not limited here. The diameter of the first natural mineral material can be 3 nm, 10 nm, 30 nm, 60 nm, 90 nm, 100 nm, etc., or other values ​​within the above range, which are not limited here. In this application, the first mineral material is fibrous and has a rich nanoporous structure, which can significantly improve the liquid absorption of the composite membrane. Furthermore, the fibrous first mineral material is also interleaved and stacked to form pores, further enhancing the liquid absorption performance of the composite membrane.

[0069] In some embodiments, the second natural mineral material includes montmorillonite.

[0070] In some embodiments, the particle size of the second natural mineral material is 0.4 μm to 3 μm. As an example, the particle size of the second natural mineral material can be 0.4 μm, 1 μm, 2 μm, 3 μm, etc., or other values ​​within the above range, and is not limited here. The second natural mineral material has a two-dimensional layered structure and excellent ion exchange properties, which can significantly improve the ionic conductivity of the composite membrane.

[0071] Based on the above, the coating contains both a first natural mineral material and a second natural mineral material. Under the synergistic effect of the first and second natural mineral materials, the liquid absorption and ionic conductivity of the composite membrane can be significantly improved.

[0072] In some embodiments, the coating also includes thickeners, adhesives, and additives.

[0073] In some embodiments, the mass ratio of modified ceramic material, natural mineral material, modified polyvinyl alcohol, thickener, adhesive, additive, and crosslinking agent is (50~80):(10~40):(2~10):(0.5~5):(3~10):(0~3):(0.03~0.4). As an example, the mass ratio of modified ceramic material, natural mineral material, modified polyvinyl alcohol, thickener, adhesive, additive, and crosslinking agent can be 50:10:2:0.5:3:0:0.03, 60:30:6:2.5:7:2:0.2, 80:40:10:5:10:3:0.4, etc., and of course, other ratios within the above range are also possible, which are not limited here.

[0074] It is understandable that the mass ratio of modified ceramic materials, natural mineral materials, modified polyvinyl alcohol, thickeners, adhesives, additives, and crosslinking agents affects the final thermal stability, mechanical strength, ionic conductivity, and puncture resistance of the composite diaphragm. By controlling the mass ratio of each substance in the composite diaphragm coating within the above-mentioned range, the combined effect of modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol can be fully utilized to effectively improve the performance of the composite diaphragm. For example, if the amount of modified ceramic material is lower than the above range, the heat resistance of the diaphragm will be reduced; if the amount of modified ceramic material is higher than the above range, the ionic conductivity of the diaphragm will be reduced.

[0075] In some embodiments, the thickener includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, and sodium alginate, guar gum, or terpineol. As an example, the thickener may include carboxymethyl cellulose or sodium carboxymethyl cellulose.

[0076] In some embodiments, the adhesive includes at least one selected from polyacrylic acid, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, polyethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane, urethane blends, or copolymers. As an example, the adhesive may be polyacrylic acid or polymethyl methacrylate.

[0077] In some embodiments, the additive includes at least one selected from fluoroalkyl ethoxylates, polyoxyethylene alkylamides, fatty alcohol polyoxyethylene ethers, sodium butadiene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, fatty acid glycerides, or polysorbates. As an example, the additive may be a fluoroalkyl ethoxylate or a polyoxyethylene alkylamide.

[0078] In some embodiments, the base film includes a polyolefin film.

[0079] In some embodiments, the polyolefin includes at least one of polyethylene and polypropylene. As an example, the polyolefin may be polyethylene or polypropylene.

[0080] In some embodiments, the thickness of the base film is 3 μm to 20 μm, and the porosity is 20% to 60%. For example, the thickness of the base film can be 3 μm, 7 μm, 13 μm, 18 μm, 20 μm, etc., or other values ​​within the above range, which are not limited here. The porosity can be 20%, 40%, 60%, etc., or other values ​​within the above range, which are not limited here.

[0081] Firstly, by limiting the thickness of the base film within the aforementioned range, the composite separator meets the mechanical strength requirements without significantly reducing ionic conductivity, maintaining a low internal resistance in the battery and minimizing negative impacts on charge / discharge efficiency and power output. Secondly, by limiting the porosity of the base film within the aforementioned range, the composite separator can absorb more electrolyte, thereby improving the uniformity of electrolyte distribution within the battery and contributing to enhanced ionic conductivity and overall electrochemical performance. Simultaneously, with the base film porosity within this range, the mechanical strength of the composite separator is not too low, making it less prone to damage during battery use or assembly.

[0082] In some embodiments, the coating thickness is 0.5 μm to 5 μm. For example, the coating thickness can be 0.5 μm, 1.5 μm, 2.6 μm, 3 μm, 4.5 μm, 5 μm, etc., or other values ​​within the above range, and is not limited here. If the coating thickness is less than 0.5 μm, there will be gaps in the coating, resulting in poor heat resistance of the separator; if the coating thickness is greater than 5 μm, it will lead to a decrease in the energy density of the battery cell, failing to meet the usage requirements.

[0083] [Preparation of Composite Separator] According to another aspect of this application, embodiments of this application provide a method for preparing a composite separator, the method comprising: Modified ceramic materials, natural mineral materials, modified polyvinyl alcohol, thickener, adhesive and additives are mixed in a solvent to obtain a suspension. Then, a crosslinking agent and catalyst are added to the suspension and mixed to obtain a coating slurry. A coating slurry is applied to at least one side of the base membrane to obtain a composite membrane.

[0084] In this application, a coating is prepared using modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol as the main materials. After being coated on both sides of a base membrane, the membrane is dried under normal pressure to obtain a composite membrane with excellent comprehensive performance. The prepared composite membrane coating has a more stable structure, and the composite membrane also has superior thermal stability, mechanical strength, ionic conductivity, and puncture resistance.

[0085] In some embodiments, the crosslinking agent is 5% to 20% of the total mass of the suspension, based on the total mass of the suspension. As an example, the crosslinking agent can be 5%, 10%, 15%, 20% of the total mass of the suspension, etc., or other values ​​within the above range, which are not limited here.

[0086] In some embodiments, the catalyst is 0.01% to 10% of the total mass of the suspension, based on the total mass of the suspension. As an example, the catalyst can be 0.01%, 0.1%, 1%, 3%, 5%, 7%, 9%, 10% of the total mass of the suspension, etc., or other values ​​within the above range, which are not limited here.

[0087] In some embodiments, the solid content of the coating slurry is 20-50%. As an example, the solid content of the coating slurry can be 20%, 30%, 40%, 50%, etc., or other values ​​within the above range, which are not limited here.

[0088] In some embodiments, the crosslinking agent includes at least one of glutaraldehyde or glyoxal. As an example, the crosslinking agent may be glutaraldehyde or glyoxal.

[0089] In some embodiments, the catalyst includes at least one of hydrochloric acid or sulfuric acid. As an example, the catalyst may be sulfuric acid or hydrochloric acid.

[0090] In some embodiments, after the slurry coating is completed, a drying step is also included, with a drying temperature of 40~60°C, preferably 45°C or 55°C; and a drying time of 30~120 min, preferably 60 min.

[0091] [Preparation of Modified Ceramic Materials] In some embodiments, the method for preparing the modified ceramic material includes: The ceramic material is added to an alcohol solution containing a silane coupling agent, and after mixing, a suspension is obtained. After adjusting the pH value, the reaction yields the modified ceramic material.

[0092] In some embodiments, the mass ratio of silane coupling agent to ceramic material is (5~15):1. As an example, the mass ratio of silane coupling agent to ceramic material can be 5:1, 10:1, 15:1, etc., or other ratios within the above range, which are not limited here.

[0093] In some embodiments, the ceramic material in the modified ceramic material includes at least one of alumina, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP (lithium aluminum titanium phosphate), LAGP, LLZO, LCZP, or LiSICON. As an example, the ceramic material in the modified ceramic material may be alumina or boehmite.

[0094] LAG is a solid-state electrolyte material based on the NASICON structure, belonging to conductive microcrystalline glass or ceramic materials. It is prepared through the crystallization treatment of a base glass and consists of a conductive crystalline phase and a residual glass phase. LLZO (Li7La3Zr2O) 12 Lithium-ion fast conductor (LCZP) is a garnet-type solid electrolyte material. Its structure is based on the crystal framework of garnet-type silicates, but it forms an inorganic non-metallic compound by replacing silicon atoms with metal atoms such as lithium (Li), lanthanum (La), and zirconium (Zr). 1.2 Ca 0.1 Zr 1.9 (PO4)3 (LCZP) is a calcium-doped zirconium-based lithium phosphate fast-ion conductor, belonging to the NASICON-type solid electrolyte. LiSICON refers to LISICON-type materials, which are sulfide-based solid electrolyte materials. Their structure is based on traditional LISICON-type oxide electrolytes but formed by partially replacing oxygen (O) with sulfur (S). A typical example is Li... 10 GeP2S 12 .

[0095] In some embodiments, the silane coupling agent used for silane coupling agent-modified ceramic materials includes at least one of γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane. As an example, the silane coupling agent used for silane coupling agent-modified ceramic materials may be γ-aminopropyltriethoxysilane or N-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0096] In some embodiments, the solid content in the suspension is 4% to 6%. As an example, the solid content in the suspension can be 4%, 5%, 6%, etc., or other values ​​within the above range, which are not limited here.

[0097] In some embodiments, the pH value is adjusted to 3-5. As an example, the pH value can be adjusted to 3, 4, 5, etc., or other values ​​within the above range, which are not limited here.

[0098] In some embodiments, the pH adjuster includes acetic acid.

[0099] In some embodiments, the reaction temperature is 50°C to 80°C, and the reaction time is 2 hours to 4 hours. As examples, the reaction temperature can be 50°C, 60°C, 70°C, 80°C, etc., or other values ​​within the above range, which are not limited here. The reaction time can be 2 hours, 3 hours, 4 hours, etc., or other values ​​within the above range, which are not limited here.

[0100] In some embodiments, the preparation of modified ceramics further includes ethanol washing and vacuum drying steps. The ethanol washing is performed 2-4 times, and the vacuum drying temperature is 60-80°C for 6-12 hours.

[0101] [Preparation of Modified Polyvinyl Alcohol] In some embodiments, the preparation of modified polyvinyl alcohol includes: Triethylene alcohol and water-soluble silicone oil are added to an aqueous solution of polyvinyl alcohol, and the reaction yields a solution containing modified polyvinyl alcohol.

[0102] In some embodiments, the molecular weight of polyvinyl alcohol is 80,000 to 120,000. As an example, the molecular weight of polyvinyl alcohol can be 80,000, 100,000, 120,000, etc., or of course, other values ​​within the above range, which are not limited here.

[0103] In some embodiments, the mass fraction of the polyvinyl alcohol aqueous solution is 10% to 15%. As an example, the mass fraction of the polyvinyl alcohol aqueous solution can be 10%, 13%, 15%, etc., or other values ​​within the above range, which are not limited here.

[0104] In some embodiments, the mass ratio of polyvinyl alcohol, trivinyl alcohol, and water-soluble silicone oil is 100:(2~2.5):(1~1.5). As an example, the mass ratio of polyvinyl alcohol, trivinyl alcohol, and water-soluble silicone oil can be 100:2:1, 100:2.3:1.2, 100:2.5:1.5, etc., and of course, other ratios within the above range are also possible, which are not limited here.

[0105] According to another aspect of this application, an embodiment of this application provides a battery including a composite separator, wherein the composite separator is the aforementioned composite separator or a composite separator prepared according to the aforementioned preparation method.

[0106] Because this battery contains the composite separator provided in the embodiments of this application, it has superior cycle performance, rate performance and safety performance.

[0107] In this embodiment, the materials and structures of the positive electrode current collector, the conductive agent and the binder in the positive electrode active material layer are not limited, and the positive electrode structure and composition known in the art that can be used in secondary batteries can be selected.

[0108] In this embodiment, the materials and structures of the negative electrode current collector, the conductive agent and the binder in the negative electrode active material layer are not limited, and the positive electrode structure and composition known in the art that can be used in batteries can be selected.

[0109] It should also be noted that the battery of this application does not limit the specific material or type of electrolyte, and can use any components and types known in the art that can be used in batteries, as long as they can achieve the purpose of this application.

[0110] Since the battery provided in this embodiment of the invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought about by the technical solutions of the above embodiments, and will not be described in detail here.

[0111] The following describes the implementation methods of this application. The implementation methods described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the implementation methods, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents, materials, or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0112] Example 1 Preparation of modified ceramic materials: γ-aminopropyltriethoxysilane was added to anhydrous ethanol and stirred for 30 min to prepare a solution. Then, alumina was added and stirred to disperse, resulting in a suspension with a solid content of 5%. Acetic acid was added to adjust the pH to 4. The mass ratio of γ-aminopropyltriethoxysilane to alumina in the suspension was 10:1. The suspension was then heated to 60 °C and reacted for 3.5 h. The powder was washed with anhydrous ethanol and filtered three times. Finally, it was dried at 80 °C for 12 h to obtain modified alumina.

[0113] Preparation of modified polyvinyl alcohol: Polyvinyl alcohol was added to deionized water and heated to 90°C and stirred for 4 hours to dissolve, resulting in a 10% polyvinyl alcohol solution. Then, trivinyl alcohol and water-soluble silicone oil were added and heated to 50°C and stirred for 4 hours to obtain a modified polyvinyl alcohol solution, wherein the mass ratio of polyvinyl alcohol, trivinyl alcohol and water-soluble silicone oil was 100:2:1.

[0114] Preparation of composite membrane: A modified polyvinyl alcohol solution was added to modified alumina (0.5 μm particle size), palygorskite (500 nm length, 50 nm diameter), and montmorillonite (0.5 μm particle size), followed by the addition of deionized water to prepare a suspension with a solid content of 40%. Then, sodium carboxymethyl cellulose (thickener), polyacrylic acid (adhesive), and fatty alcohol polyoxyethylene ether (auxiliary agent) were added, and deionized water was added again. The mixture was stirred to obtain a suspension with a solid content of 35%. The solid content of the suspension consisted of 59.9% modified alumina by mass, 30% palygorskite and montmorillonite by mass (with a mass ratio of 1:2), 5% modified polyvinyl alcohol, 4% adhesive, 1% thickener, and 0.1% auxiliary agent. Then, glutaraldehyde and hydrochloric acid were added to the coating solution and stirred to obtain the coating solution. The amount of glutaraldehyde added accounted for 10% of the total mass of the suspension, and the amount of hydrochloric acid accounted for 0.5% of the total mass of the suspension. The coating was applied to one side of a 7μm polyethylene film along its own thickness direction using a wire rod, and baked at 60℃ for 60 min to obtain a composite diaphragm with a coating thickness of 3μm.

[0115] Example 2 The difference between Example 2 and Example 1 is that in Example 2, the mass ratio of γ-aminopropyltriethoxysilane to alumina is 5:1 when preparing the modified ceramic material.

[0116] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the mass ratio of γ-aminopropyltriethoxysilane to alumina is 15:1 when preparing the modified ceramic material.

[0117] Example 4 The difference between Example 4 and Example 1 is that, in Example 4, when preparing the composite membrane, the mass percentage of modified alumina in the suspension solids content is 79.9%, the total mass percentage of palygorskite and montmorillonite is 10%, wherein the mass ratio of palygorskite and montmorillonite is 1:2, the mass percentage of modified polyvinyl alcohol is 5%, the mass percentage of adhesive is 4%, the mass percentage of sodium carboxymethyl cellulose is 1%, and the mass percentage of additives is 0.1%.

[0118] Example 5 The difference between Example 5 and Example 1 is that, in Example 5, when preparing the composite membrane, the mass percentage of modified alumina in the suspension solids is 49.9%, the total mass percentage of palygorskite and montmorillonite is 10%, with the mass ratio of palygorskite to montmorillonite being 1:2, the mass percentage of modified polyvinyl alcohol is 5%, the mass percentage of adhesive is 4%, the mass percentage of sodium carboxymethyl cellulose is 1%, and the mass percentage of additives in the coating liquid is 0.1%.

[0119] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the mass ratio of palygorskite to montmorillonite is 4:1.

[0120] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the mass ratio of palygorskite to montmorillonite is 1:4.

[0121] Example 8 The difference between Example 8 and Example 1 is that, in Example 8, when preparing the composite membrane, the mass percentage of modified alumina in the suspension solids content is 62.9%, the total mass percentage of palygorskite and montmorillonite is 30%, wherein the mass ratio of palygorskite to montmorillonite is 1:2, the mass percentage of modified polyvinyl alcohol is 2%, the mass percentage of adhesive is 4%, the mass percentage of sodium carboxymethyl cellulose is 1%, and the mass percentage of additives is 0.1%.

[0122] Example 9 The difference between Example 9 and Example 1 is that, in Example 9, when preparing the composite membrane, the mass percentage of modified alumina in the suspension solids content is 54.9%, the total mass percentage of palygorskite and montmorillonite is 30%, wherein the mass ratio of palygorskite and montmorillonite is 1:2, the mass percentage of modified polyvinyl alcohol is 10%, the mass percentage of adhesive is 4%, the mass percentage of sodium carboxymethyl cellulose is 1%, and the mass percentage of additives is 0.1%.

[0123] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the modified alumina was replaced with alumina.

[0124] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the mass percentage of modified alumina in the suspension solids content is 93.9%, and the total mass percentage of palygorskite and montmorillonite is 0%.

[0125] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the mass percentage of palygorskite in the suspension is 0, and the mass percentage of montmorillonite is 30%.

[0126] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the mass percentage of palygorskite in the suspension is 30%, and the mass percentage of montmorillonite is 0%.

[0127] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the mass percentage of modified alumina in the suspension solids content is 64.9%, the mass percentage of modified polyvinyl alcohol is 0%, and glutaraldehyde and hydrochloric acid are not added.

[0128] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that modified alumina was replaced with alumina, and the mass percentage of alumina in the solid content of the suspension was 64.9%, the mass percentage of modified polyvinyl alcohol was 0%, and glutaraldehyde and hydrochloric acid were not added.

[0129] Performance testing The composite membranes prepared according to the above embodiments and comparative examples were tested, as follows: 1. The test methods for needle penetration strength, heat shrinkage rate and ionic conductivity shall be in accordance with the national standard GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".

[0130] 2. Peel strength test: Cut the diaphragm into strips 25mm wide and 200mm long, stick the coated side to the surface of 3M tape, and use a universal tensile testing machine to test at a speed of 50mm / min.

[0131] 3. Contact angle test: Use a contact angle tester to test.

[0132] 4. Liquid absorption rate test: Cut the diaphragm into a size of 2.5cm×20cm, weigh it and record its mass as m1, and then completely immerse it in 1 M LiPF6 electrolyte (the solvent is a mixed solvent of ethylene carbonate, methyl ethyl carbonate and diethyl carbonate in a volume ratio of 1:1:1). After soaking for 1 hour, take it out, wipe off the excess electrolyte on the surface with lint-free paper, weigh it and record it as m2. The liquid absorption rate is (m2-m1) / m1×100%.

[0133] 5. Battery performance test Battery manufacturing Preparation of the positive electrode sheet: The positive electrode active material lithium iron phosphate, the binder polyvinylidene fluoride (PVDF), and the dispersant are mixed in a mass ratio of 97.88:2:0.12. Then, N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed uniformly to form a stable positive electrode slurry with a solid content of 65%. The positive electrode slurry is uniformly coated on a 13μm aluminum foil of the positive electrode current collector. After drying, cold pressing, and slitting, the positive electrode sheet is obtained.

[0134] Preparation of negative electrode sheet: Artificial graphite, conductive carbon black (SP), carboxymethyl cellulose, and styrene-butadiene rubber are mixed in a mass ratio of 96.5:1:1:1.5, then deionized water is added, and the mixture is stirred and homogenized to form a stable negative electrode slurry with a solid content of 49%. The negative electrode slurry is uniformly coated on an 8μm copper foil of the negative electrode current collector, and then dried, cold-pressed, and slit to obtain the negative electrode sheet.

[0135] Electrolyte: In a glove box filled with inert gas, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate are mixed in a mass ratio of 1:1:1 to obtain an organic solvent. Then, lithium salt LiPF6 is dissolved in the organic solvent at a concentration of 1 mol / L to obtain the electrolyte.

[0136] Battery assembly: The positive electrode, composite separator, and negative electrode are assembled, and then injected with electrolyte, encapsulated, and formed to produce a 5Ah soft-pack battery.

[0137] Capacity retention rate test after 1000 cycles: The test temperature is 25℃. The battery is charged to 3.65V at a current density of 1C, and the initial charge capacity is recorded. Then, it is charged at a constant voltage of 3.65V until the current reaches 0.05C (cutoff point), and then discharged at 1C to 2V. The initial discharge capacity is recorded. The capacity retention rate after the 1000th cycle is recorded. The capacity retention rate after the 1000th cycle is calculated as: (Discharge capacity after 1000 cycles / Initial discharge capacity) × 100%.

[0138] The specific test results are shown in Table 1.

[0139] Table 1 Note: In Table 1, MD direction refers to the longitudinal direction and TD direction refers to the transverse direction.

[0140] As shown in Table 1, compared to Comparative Examples 1-6, the composite membranes prepared in Examples 1-9 all exhibit superior mechanical strength, heat resistance, ionic conductivity, and adhesion between the ceramic coating and the substrate. The assembled lithium-ion batteries also demonstrate better cycle performance. This indicates that modifying the ceramic with a coupling agent to introduce polar groups on the surface, and combining it with palygorskite and montmorillonite, natural minerals containing polar groups and having nanoporous structures, can significantly improve the wettability, absorbency, and ionic conductivity of the membrane. Furthermore, montmorillonite, with its two-dimensional layered structure, provides more electrolyte storage channels and possesses excellent ion exchange properties, further enhancing the membrane's absorbency and ionic conductivity. Palygorskite, being one-dimensional fibrous, is interleaved and stacked in the coating, serving as a mechanical support framework to inhibit membrane shrinkage at high temperatures and improving the membrane's puncture resistance. Introducing amphiphilic modified polyvinyl alcohol into the coating can promote interfacial bonding between the inorganic ceramic, natural mineral, and polyolefin substrate or adhesive, thereby improving the membrane's peel strength. In addition, under the action of crosslinking agents, modified polyvinyl alcohol undergoes in-situ crosslinking with modified ceramics and natural minerals to form a three-dimensional network structure, which can improve the puncture resistance of the diaphragm.

[0141] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0142] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.

[0143] It should be noted that the terms "and / or" or " / " used herein are merely descriptions of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. The singular forms "a," "described," and "the" used in the embodiments of the invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0144] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A composite diaphragm, characterized in that, Includes a base film and a coating disposed on at least one surface of the base film along the thickness direction; The coating comprises modified ceramic materials, natural mineral materials, and modified polyvinyl alcohol; The modified ceramic material includes a first hydrophilic group and a first lipophilic group; The modified polyvinyl alcohol includes a second hydrophilic group and a second lipophilic group; The first hydrophilic group includes at least one of hydroxyl and amino groups; The first lipophilic group includes at least one of methoxy, ethoxy, methyl, ethyl, propyl, and silyl groups; The second hydrophilic group includes a hydroxyl group; The second lipophilic group includes a siloxane group; The natural mineral material includes a first natural mineral material and a second natural mineral material. The first natural mineral material includes at least one of halloysite, palygorskite, attapulgite, zeolite, or sepiolite, and the second natural mineral material includes montmorillonite.

2. The composite diaphragm according to claim 1, characterized in that, The modified ceramic material has a particle size of 100 nm to 3 μm.

3. The composite diaphragm according to claim 1, characterized in that, The natural mineral material includes a first natural mineral material and a second natural mineral material; The mass ratio of the first natural mineral material to the second natural mineral material is (1~4):(1~4). The length of the first natural mineral material is 0.2 μm to 3 μm, and the diameter is 3 nm to 100 nm; The particle size of the second natural mineral material is 0.4μm to 3μm.

4. The composite diaphragm according to claim 1, characterized in that, The coating also includes thickeners, adhesives, and additives; The mass ratio of the modified ceramic material, natural mineral material, modified polyvinyl alcohol, thickener, adhesive, additive, and crosslinking agent is (50~80):(10~40):(2~10):(0.5~5):(3~10):(0~3):(0.03~0.4). The thickener includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, sodium alginate, guar gum, or terpineol. The adhesive includes at least one of polyacrylic acid, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, polyethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane, and urethane. The additives include at least one of fluoroalkyl ethoxy alcohol ethers, polyoxyethylene alkylamides, fatty alcohol polyoxyethylene ethers, sodium butadiene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, fatty acid glycerides, or polysorbates.

5. The composite diaphragm according to claim 1, characterized in that, The base membrane includes a polyolefin membrane; The polyolefin includes at least one of polyethylene and polypropylene; And / or, the thickness of the base film is 3 μm to 20 μm, and the porosity is 20% to 60%; And / or, the thickness of the coating is 0.5 μm to 5 μm.

6. The method for preparing the composite separator according to any one of claims 1 to 5, characterized in that, The preparation method includes: Modified ceramic materials, natural mineral materials, modified polyvinyl alcohol, thickener, adhesive and additives are mixed in a solvent to obtain a first suspension. Then, a crosslinking agent and catalyst are added to the first suspension and mixed to obtain a coating slurry. The coating slurry is applied to at least one surface of the base film to obtain a composite diaphragm; The catalyst includes at least one of hydrochloric acid or sulfuric acid; The additives include at least one of fluoroalkyl ethoxy alcohol ethers, polyoxyethylene alkylamides, fatty alcohol polyoxyethylene ethers, sodium butadiene naphthalene sulfonate, sodium hydroxyethyl sulfonate, sodium dodecylbenzene sulfonate, stearic acid, fatty acid glycerides, or polysorbates.

7. The method for preparing the composite diaphragm according to claim 6, characterized in that, The step of preparing the coating slurry satisfies at least one of the following features (1) to (4): (1) Based on the total mass of the first suspension, the crosslinking agent accounts for 5% to 20% of the total mass of the first suspension; (2) Based on the total mass of the first suspension, the catalyst is 0.01% to 10% of the total mass of the first suspension; (3) The solid content of the coating slurry is 20-50%; (4) The crosslinking agent includes at least one of glutaraldehyde or glyoxal.

8. The method for preparing the composite diaphragm according to claim 6, characterized in that, The preparation method of the modified ceramic material includes: The ceramic material is added to an alcohol solution containing a silane coupling agent, and after mixing, a second suspension is obtained. After adjusting the pH value, the reaction yields the modified ceramic material. The mass ratio of the silane coupling agent to the ceramic material is (5~15):1; The ceramic material in the modified ceramic material includes at least one of alumina, boehmite, zirconium oxide, silicon oxide, magnesium oxide, titanium oxide, zinc oxide, calcium oxide, barium sulfate, silicon nitride, boron nitride, aluminum nitride, silicon carbide, LATP, LAGP, LLZO, LCZP or LiSICON. The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, N-β-aminoethyl-γ-aminopropyltrimethoxysilane or γ-methacryloxypropyltrimethoxysilane; The solid content in the second suspension is 4% to 6%; The pH value is adjusted to 3-5; The reaction temperature is 50℃~80℃, and the time is 2h~4h.

9. The method for preparing the composite diaphragm according to claim 6, characterized in that, The preparation of the modified polyvinyl alcohol includes: Trivinyl alcohol and water-soluble silicone oil are added to an aqueous solution of polyvinyl alcohol, and the reaction yields a solution containing modified polyvinyl alcohol. The molecular weight of the polyvinyl alcohol is 80,000 to 120,000; The mass fraction of the polyvinyl alcohol aqueous solution is 10%~15%; The mass ratio of polyvinyl alcohol, trivinyl alcohol and water-soluble silicone oil is 100:(2~2.5):(1~1.5).

10. A battery, comprising a separator, characterized in that, The diaphragm is the composite diaphragm according to any one of claims 1 to 5 or the composite diaphragm prepared by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Lithium ion battery diaphragm with modified ceramic coating

    CN118712663A

  • Diaphragm, preparation method thereof and lithium ion battery

    CN119994380A